Economic Complexity and Human Development How economic diversification and social networks affect human agency and welfare - Hartmann, Dominik (Routledge Studies in Development Economics, 2014)
This book combines the human development approach and innovation economics in order to explore the effects that structural economic change has on human development. The author discusses how innovation, social networks, economic dynamics and human development are interlinked, and provides several practical examples of social and micro-entrepreneurship in contexts as diverse as Peruvian rural villages and Brazil's urban areas